Algorithmic foundations of economic and mathematical modeling of network logistics processes - Sergey Yevgenievich Barykin; Irina Vasilievna Kapustina; Sergey Mikhailovich Sergeev; Vladimir Konstantinovich Yadykin (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Nowadays, digitizing the data stream is enabling the evolution of logistics processes. The data-driven network logistics processes are evaluated by leading economic indicators. The purpose of this study is to further develop the algorithmic foundations of economic and mathematical modeling of logistics networks based on advanced technologies that the digitalization process provides. Methods of mathematical modeling of flows of various resources in logistic networks, the structure of which is presented in the form of a graph, are used in the work. The economic benefit lies in the implementation of the planning concept based on leading indicators. As a result, using a set of formalisms, a mathematical model has been developed, which will make it possible to search for optimal solutions based on the criterion of economic efficiency. The results obtained will find application not only in transport problems. Network logistics includes the transportation of liquid and gaseous materials through pipelines, energy through electrical networks. A universal mathematical model will allow the results to be applied in many industries and economic activities when it is required to make economically sound decisions based on a stream of digital data coming in real time.
Keywords: 650; digital logistics; logistics network; simulation model; smart supply chains